2018
DOI: 10.1080/03009734.2018.1521890
|View full text |Cite
|
Sign up to set email alerts
|

Changes of arterial pressure following relief of obstruction in adults with hydronephrosis

Abstract: Background: As much as 20% of all cases of hypertension are associated with kidney malfunctions. We have previously demonstrated in animals and in pediatric patients that hydronephrosis causes hypertension, which was attenuated by surgical relief of the ureteropelvic junction (UPJ) obstruction. This retrospective cohort study aimed to investigate: (1) the proposed link between hydronephrosis, due to UPJ obstruction, and elevated arterial pressure in adults; and (2) if elevated blood pressure in patients with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In our adult study, there was no signi cant difference in the prevalence of de ned HTN pre-and post-intervention. In contrast, a retrospective analysis of 49 adults with congenital UPJO (not on antihypertensive medications) showed improvement in both systolic and diastolic BP after surgical intervention; however, these ndings were based predominantly on data ≤ 12 months after relief of obstruction 13 . For our non-intervention group, there were no signi cant differences between the initial and follow-up measures of de ned HTN and median BP.…”
Section: Discussionmentioning
confidence: 90%
“…In our adult study, there was no signi cant difference in the prevalence of de ned HTN pre-and post-intervention. In contrast, a retrospective analysis of 49 adults with congenital UPJO (not on antihypertensive medications) showed improvement in both systolic and diastolic BP after surgical intervention; however, these ndings were based predominantly on data ≤ 12 months after relief of obstruction 13 . For our non-intervention group, there were no signi cant differences between the initial and follow-up measures of de ned HTN and median BP.…”
Section: Discussionmentioning
confidence: 90%
“…It has been demonstrated that the function of the hydronephrotic kidney is rather well-preserved in young children, therefore it appears that the intrarenal mechanism leading to hypertension is also reversible (6,11). The clinical importance of such finding is that surgical management may prevent the development of chronic hypertension and associated comorbidities in patients with severe hydronephrosis (68)(69)(70). The pediatric urologist and nephrologist may have to pay more attention to the risk of development of high blood pressure in patients with severe hydronephrosis (Figure 2).…”
Section: Hypertensionmentioning
confidence: 99%